The rich diversity of seed supply - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Four out of every five seeds acquired by farmers in ACP countries come through traditional seed supply systems. The last ten years has seen a renaissance in these networks, with many different methods. They are all networks, and our advice is to...